DEVELOPMENT OF NUMERACY LITERACY MODULE ON MEASUREMENT MATERIAL IN ISLAMIC ELEMENTARY SCHOOL - Muhammad Ilman Nafi'an (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
This study aims to develop a design and test the feasibility of numeracy literacy modules, as well as see the response of students. Modules are important in the learning process but teachers still convey concepts orally, limited reading books, inadequate learning resources so that students' numeracy literacy skills are low.  This research involved 29 students of class III PKBM Quins Tulungagung for the trial. The type of research and development in this study is using Research and Development (RD) with the ADDIE model (Analyze, Design¸ Develop, Implement, and Evaluate). The instruments in this study were interviews, observations, documentation, questionnaires assessed by material experts and teaching material experts, and student response questionnaires. The results showed that (1) the validation results showed that the learning module was feasible to use in the learning process with an average score of 3.7 and 3.8. (2) the results of the initial field trial showed that the learning module was feasible to use in the learning process with an average score of 1.97 while the results of the operational field trial showed that the learning module was feasible to use in the learning process with an average score of 1.92. For this reason, future researchers can develop numeracy literacy modules for other material concepts and conduct wider trials.